Rola Trebnika św. Piotra Mohyły w zachowaniu tożsamości religijnej rodzin ukraińskich .......... 93 - Michałko, Anna (Tożsamość i pamięć : konteksty kulturowe i społeczne. Studia ukrainoznawcze, 2021)
THE ROLE OF THE TREBNIK BY ST. PETRO MOHYLA IN PRESERVING THE RELIGIOUS IDENTITY OF UKRAINIAN FAMILIESThe religious identity of the time of the Kiev metropolitan Saint Petro Mohyla was inseparable from the national identity. The theological works of Petro Mohyla, especially Trebnik from 1646, had influenced the preservation of the religious identity of Ukrainian families. Joint participation in the liturgy, continuation of traditional rites strengthened family ties, basing on respect for the older generation, identification with the heritage of ancestors and building a sense of belonging to the community – the nation.